Association of serum intact parathyroid hormone levels with sarcopenia in patients undergoing peritoneal dialysis - Hsu, Bang-Gee; Wang, Chih-Hsien; Tsai, Jen-Pi; Chen, Yi-Hsin; Hung, Szu-Chun; Lin, Yu-Li (Frontiers in Medicine, 2024)
Objective: Sarcopenia is highly prevalent in patients undergoing peritoneal dialysis (PD), contributing to adverse clinical outcomes. Animal models suggest that parathyroid hormone (PTH) induces muscle wasting through adipose tissue browning. However, the relationship between PTH dysregulation and sarcopenia in the PD population remains unclear. Thus, we aimed to explore the association between serum intact PTH levels and sarcopenia in PD patients.We conducted a cross-sectional analysis using data from the Tzu-Chi PD cohort, comprising 186 PD patients with a mean age of 57.5 ± 14.1 years. Basic information, comorbidities, serum intact PTH levels, and other biochemical data were retrieved. Atherosclerotic cardiovascular disease (ASCVD) includes any history of coronary artery disease, myocardial infarction, peripheral arterial disease, and stroke. All patients were evaluated for appendicular skeletal muscle mass (ASM) using the Body Composition Monitor (BCM), handgrip strength, and 6-meter usual gait speed.Sarcopenia was defined based on the consensus of the Asian Working Group for Sarcopenia 2019.Relative over-hydration (OH) was also assessed using BCM.The overall prevalence of sarcopenia was 38.2%. Across three groups of intact PTH levels (< 150 pg/mL, 150-300 pg/mL, and > 300 pg/mL), the prevalence rates of sarcopenia were 29.7%, 36.4%, and 46.2%, respectively (p for trend = 0.044). In the unadjusted model, age, ASCVD, subjective global assessment score, body mass index, relative OH, serum albumin, creatinine, phosphorus, and log-transformed intact PTH levels were significantly associated with sarcopenia.After full adjustment for all above factors, age (odds ratio [OR] = 1.04, 95% confidence interval [CI] = 1.00-1.08), ASCVD (OR = 4.12, 95% CI = 1.34-12.65), BMI (OR = 0.51, 95% CI = 0.41-0.64), relative OH (OR = 1.04, 95% CI = 1.00-1.07), log-transformed intact PTH levels (OR = 3.72, 95% CI = 1.51-9.14) were independently associated sarcopenia among PD patients.Among PD patients, elevated serum intact PTH levels are independently associated with sarcopenia.Further longitudinal studies are warranted to confirm their causal relationship.